DISTINCT a digital simulation study in cane sugar technology - Ramirez, Alex G.
This study discusses the use of System Dynamics in analyzing behavior of a sugar manufacturing process over a period of time. A case of the raw sugar manufacturing at the Southern Negros Development Corporation (SONEDCO) is chosen to demonstrate the uses of such techniques. The study discusses the manner in which the process was analyzed. Details are given of the techniques used in the formulation of a mathematical model for use in obtaining the material balances at the various processing stations around the factory. Specific relationships among the variables and suitable empirical equations were developed to fit into the construction of a logic system or program of instruction for the comp0uter. A computer program called DYNAMO is used to simulate the System Dynamics model developed.